Evaluation of total antioxidant capacity of serum after strenuous endurance exercise - Kawai, Y.; Iwane, H.; Takanami, Y.; Shimomitsu, T.; Katsumura, T. (Medicine & Science in Sports & Exercise, 1996)
The total antioxidant capacity of serum after strenuous endurance exercise was evaluated. Male triathletes (N = 29) performed a full competitive triathlon. Blood samples were taken immediately before, after, and one day after the performance. It was found that total antioxidant capacity of serum was enhanced after the triathlon due to the mobilization of antioxidants and the synergism between antioxidants. Implication. Endurance exercise mobilizes antioxidants.